Developing Physics Teaching Materials Based on Differentiated Merdeka Curriculum Using an Ethnoscience-Integrated Contextual Approach - Fianti, Fianti; Neratania, Alvina (Faculty of Mathematics and Natural Sciences, Universitas Negeri Yogyakarta, 2024)
The availability of Merdeka Curriculum teaching materials in schools is still lacking, so it is necessary to develop Merdeka Curriculum teaching materials to support dynamic learning. For this reason, teaching materials were developed in the form of a book with the title Student's Book Getting to Know Indonesian Culture and Physics through Various Concepts of Particle Motion Dynamics for Class XI SMA/MA/Equivalent. This research aims to (1) describe the characteristics, (2) measure and assess feasibility, and (3) measure and assess the practicality of Merdeka Curriculum-based physics teaching materials differentiated with an ethnoscience-integrated contextual approach. The research method used is the research and development (R&D) method with a 4D model (define, design, develop, and disseminate). The define stage involves analyzing needs, the design stage involves designing teaching materials and compiling assessment instruments, the development stage involves realizing the design and assessing feasibility and practicality, and the dissemination stage is carried out through distributing teaching materials. Based on the results of data analysis, this teaching material has characteristics according to students' needs which includes contextual differentiation learning in traditional Indonesian game culture. The feasibility and practicality test results show 91.25% and 87.66% of the materials are in very high criteria.